PUBLIC RESPONSE TO HALAL CERTIFICATION AND LABELLING OF PALEMBANG SPECIAL FOOD TOWARDS PALEMBANG DARUSSALAM VISION - Irham Falahudin; Delia Yusfarani; Ike Apriani (Universitas Mathla’ul Anwar Banten, 2021)
Palembang City has many variants of typical or traditional food. Palembang specialties such as pempek, laksan, burgo, tekwan are ingredients of local processed products. However, at this time food processing is very complex, many of the manufacturers in food processing use technology, additives such as dyes or other substances. This composition makes it important for consumers to know about its halalness. This knowledge is important to know how the public responds to whether a product is halal or not. Currently, there are still many typical foods of Palembang City that do not have halal certification and labeling by LPPOM MUI. This study aims to determine the public's response to halal certification and labeling on Palembang typical food products, towards the vision of the city of Palembang Darussalam in realizing halal culinary tourism. The study, which was conducted from May-September 2020, used quantitative methods by collecting data using a questionnaire with 105 respondents. Then to see typical Palembang foods that are halal and Thayyib, a qualitative food test was carried out. The results of the research on the qualitative test of food were negative for borax and there were five samples containing formaldehyde. The public's response to knowledge of halal certification and labeling on Palembang specialties is directly proportional to the vision of the city of Palembang.